Association analysis of Epworth Sleepiness Scale (ESS) scores with serotonin transporter (5-HTT- LPR, 5-HTT-VNTR) and circadian (PER3-VNTR) genes - Ozen, Filiz; Yegin, Zeynep; Saglam, Zuhal Aydan; Yavlal, Figen; Koc, Haydar; Ulasoglu, Celal (Sleep Science, 2022)
Excessive daytime sleepiness (EDS) is a common complaint encountered in clinical practice with serious consequences both for individual and society since it can increase the ratio of motor vehicle accidents, work- related incidents, and deaths. Moreover, it also manifests less serious individual consequences. This study aimed to investigate the potential role of PER3-VNTR, 5-HTT-LPR, and 5-HTT-VNTR in terms of constituting liability to EDS. Two hundred eighteen participants (93 complaining about daytime sleepiness and 125 individuals with no serious complaint) were recruited in the study. General daytime of sleepiness was quantified with Epworth sleepiness scale (ESS). DNA extractions were performed from collected blood samples with standart salting-out procedure and genotyped. ESS scores displayed difference between individuals suffering from sleep disturbances and other individuals with values of 12.75±4.55 and 6.34±4.26, respectively. PER3- VNTR and 5-HTT-LPR genotypes did not display association with mean ESS scores. However, 5-HTT-VNTR genotypes showed significant association with mean ESS scores; individuals with 10/10 genotypes had the highest ESS score reflecting this genotype as a liability factor for EDS. We strongly recommend further studies based on circadian/serotonin pathway genes in different populations to reach to a consensus and highlight sleep genetic marker genes which then can be the future targets of pharmacological treatment studies for sleep problems.
Keywords: Neurogenetics; Excessive daytime sleepiness (EDS); Epworth Sleepiness Scale (ESS); PER3; Serotonin transporter (5-HTT); Genetic association